Sistem Paparan Kesihatan Menggunakan Borland C++ Builder - Karen Then, Miaw Wah (Universiti Sains Malaysia, 2005)
This project is implemented to develop a user-friendly health indicator system. The system is a graphical user interface (GUI) built using the Borland C++ Builder software. The system is to assist physicians and other medical personnel to monitor a patient’s vital signs namely the patient’s blood pressure, body temperature, oxygen level concentration in blood and heart beat rate by just glimpsing at one screen instead of having to scrutinize four separate equipments in order to get readings. In general, the system is made up of three main modules which includes; a search module, real-time monitoring module and recovery module. The search module encompasses a box to key in the patient’s name or ID and a search button to locate the patient’s file. The real-time monitoring module shows the current measurements of the health parameters on the screen. Each parameter has an alarm that will flicker should any abnormalities occur. In practical, this system should be hooked up to hardwares that interpret signals acquired from the patient and measurements are stored in a source file. Thus, this system is also implemented to retrieve the measurements from the source file and present it on the screen in numerical and graphical form.